An Automatic Tyre Inflating System (ATIS) - Sivarao, Subramonian (2012)
A novel way of automatically inflate automobile tyre, so that no more manual inflating is required. The present invention relates to an automatic tyre inflating means of a vehicle comprising: a pressure chamber fitted on a wheel hub; a pressure compensation means fixed on the pressure chamber; a relief valve fixed on the pressure chamber; a connecting hose connecting the pressure compensation means and a tyre valve stem; and an inflating means having a piston fixed on the pressure chamber; characterized in that an actuator is fixed at a brake calliper, the actuator collides with the piston of the inflating means during wheel rotation, at the same time the piston of the inflating means pressurizes the air inside the pressure chamber using collision force to compress the air.